Comparison of nutrient intake in adolescents and adults with and without food allergies. Issue 2 (13th July 2017) - Maslin, K.; Venter, C.; MacKenzie, H.; Vlieg‐Boerstra, B.; Dean, T.; Sommer, I.
Abstract: Background: Exclusion diets for the management of food allergy pose a risk of nutritional deficiencies and inadequate growth in children, yet less is known about their effect in adolescents and adults. The present study aimed to compare the dietary intake of adolescents and adults with food allergies with that of a control group. Methods: A food allergic and a control group were recruited from Portsmouth and the Isle of Wight in the UK. Participants were recruited from a food allergy charity, allergy clinics, a local school and university, and previous research studies. Macro and micronutrient intake data were obtained using a 4‐day estimated food diary. Sociodemographic and anthropometric data was collected via a constructed questionnaire. Results: This cross‐sectional study included 81 adolescents (48 food allergic and 33 controls) aged 11–18 years and 70 adults aged 19–65 years (23 food allergic and 47 controls). Overall, 19 (22.8%) adolescents and 19 (27.1%) adults took dietary supplements, with no difference according to food allergic status. Adolescents with food allergy had higher intakes of niacin and selenium than adolescents without ( P < 0.05). This difference persisted when dietary supplements were removed from the analysis. Adults with food allergies had higher intakes of folate and zinc than those without ( P < 0.05); however, this difference did not persist when dietary supplements were removed from the analysis. Across all participants, the intake of several micronutrients was suboptimal. There was no difference in protein or energy intake, or body mass index, according to food allergic status. Conclusions: The dietary intake of food allergic participants was broadly similar and, in some cases, better than that of control participants. However, suboptimal intakes of several micronutrients were observed across all participants, suggesting poor food choices.